Pilot test of a fermentation tank for producing coal methane through anaerobic fermentation - Xia, Daping; Zhang, Huaiwen; Su, Xianbo; Liu, Xile; Fu, Chaoyong (Penerbit Universiti Kebangsaan Malaysia, 2017)
The development and utilization of clean energy has long been a focus of research. In the coal bed methane field, most coal bed biogenic methane experiments are small static sample tests in which the initial conditions are set and the process cannot be batch-fed elements and microbial strains, and the gas cannot be collected in batches. Although significant results have been achieved in the coal-to-biogenic methane conversion in China, findings are restricted to the laboratory scale. No successful commercialization of coal bed biogenic methane production has been achieved yet. This study used a large-capacity fermentation tank (5 L) to conduct biogenic methane experiments. Results were compared to those from the traditional laboratory test. The gas production rate and gas concentration were higher when the 250 mL methane test volume was increased to a 5 L fermentation volume, increasing by 20.9% and 2.3%, respectively. The inhibition effect of the liquid phase products was reduced in the large fermentation tank, and the microbial activity was extended by batch feeding trace elements (iron and nickel) and methane strains and by semi-continuous collection of the gas. However, the gas conversion rate can be increased by retaining the H2 and CO2 in the intermediate gas products in the fermentation tank. The gas production rate was increased from 17.9 to 24.6 mL/g, increasing by 37.4%. The simulation pilot test can lay a foundation for the transition from a coal bed biogenic methane laboratory static small sample test to a dynamic pilot test, optimizing the process parameters to improve the reaction efficiency and move forward to commercialization test.